Menembus Batas Matematika: Strategi Pembelajaran KPK Berbasis Lompat Tali dan Dzikir (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to explore innovative learning strategies that integrate the concept of Least Common Multiple (LCM) in mathematics with physical and spiritual activities, namely jumping rope while reciting dhikr. This strategy is based on holistic learning that combines cognitive, affective, and psychomotor aspects, in accordance with the direction of the Independent Curriculum. The method used is Classroom Action Research (CAR) for two cycles implemented on grade IV Elementary School students. The results of the study showed that this approach was effective in improving students' understanding of the LCM concept, while fostering religious character and increasing students' active involvement in the learning process. The average student score increased from 60 in the pre-cycle to 84 in the second post-cycle. This strategy not only breaks through the boundaries of conventional mathematics learning which tends to be monotonous, but also strengthens spiritual values ​​and togetherness among students. The integration of dhikr into the rope jumping activity provides a fun, meaningful, and character-building learning experience.